The Existence of ‘Sasi Ikan Lompa’ in the Millenium Era: Profit or Loss? Evidence from Maluku, Indonesia - Sandanafu, Sally Paulina; Mairuhu, Dady; Sadubun, Vury Lilian Angela (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to revealed whether Sasi Ikan Lompa brings benefits or losses in modern era and how the local government particularly the Maluku Tourism Department contributes to promoting local wisdom Sasi. Data analysis techniques used a qualitative descriptive approach to explain the existence of Sasi. The results show that Sasi custom provides considerable benefits for the people’s prosperity. Thus, the existence of Sasi should be maintained for increasing community income. This research is expected to contribute ideas and policies to the related parties in empowering the potential of natural resources and their sustainability.